Pressure-sensitive adhesive protective film and preparation method thereof

By adding specific functional additives to the polyethylene film to improve its matrix performance, the problem of insufficient resistance of existing polyethylene films in ultraviolet and high temperature environments is solved, and higher UV resistance, heat resistance and mechanical properties are achieved.

CN119570141AInactive Publication Date: 2025-03-07JINWANZHENG (GUANGDONG) NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411994136.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing plastic films show insufficient resistance in ultraviolet rays and high temperature environments, which affects their service life.

Method used

High-density polyethylene is used as the main matrix, and maleic anhydride grafting low-density polyethylene, hyperbranched polyimide and reinforced filler are added to improve the compatibility, heat resistance and ultraviolet resistance of the matrix.

Benefits of technology

It significantly improves the UV resistance, heat resistance and mechanical strength of polyethylene film, extends its service life, and enhances its application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a pressure-sensitive adhesive protective film and a preparation method thereof. According to the pressure-sensitive adhesive protective film disclosed by the invention, high-density polyethylene is taken as a main matrix, and various functional aids are added, so that the comprehensive performance of a polyethylene film is improved; wherein the maleic anhydride grafted low-density polyethylene improves the compatibility among the raw materials of the components of the matrix; hyperbranched polyimide is added, so that the heat resistance and the mechanical strength of the adhesive are improved; the reinforcing filler is added, so that the ultraviolet resistance and transparency of the matrix are improved. Therefore, the polyethylene film provided by the invention has a wider application prospect when being used as a protective film of the pressure-sensitive adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a pressure-sensitive adhesive protective film and a preparation method thereof. Background Art

[0002] Pressure-sensitive adhesive is composed of substrate, pressure-sensitive adhesive, primer and back treatment agent. As one of the key factors, the substrate is not only the basic material to support the pressure-sensitive adhesive, but also needs to have good mechanical strength, uniform thickness, and not easy to deform. Common substrates generally include: plastic films, fabrics, paper, etc. Among them, plastic films have good mechanical strength and uniform thickness, are not easy to deform, and have good wettability with pressure-sensitive adhesives, making them more widely used.

[0003] Plastic films mainly include polypropylene, polyethylene, polyvinyl chloride and polyester films, among which polyethylene films have the advantages of excellent mechanical properties, cold resistance, corrosion resistance and low cost. However, this type of film also has certain disadvantages, such as: (1) poor UV resistance. Long-term exposure to ultraviolet light will damage the film, affecting its service life; (2) limited heat resistance. It may soften or even melt in high temperature environments. Therefore, it is necessary to prepare a pressure-sensitive adhesive protective film with excellent UV resistance, heat resistance and other good comprehensive properties to meet practical application needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a pressure-sensitive adhesive protective film and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions: A pressure-sensitive adhesive protective film comprises the following raw materials in parts by weight: 60-80 parts of high-density polyethylene, 8-15 parts of maleic anhydride grafted low-density polyethylene, 15-25 parts of hyperbranched polyimide, 8-15 parts of reinforcing filler, 1-2 parts of lubricant, 0.1-0.2 parts of initiator, and 1-3 parts of antioxidant; Furthermore, the lubricant is zinc stearate, the initiator is benzoyl peroxide, and the antioxidant is antioxidant 1010; The reinforcing filler is prepared by the following steps: Step A1, dispersing hexadecyltrimethylammonium bromide uniformly in deionized water, adding 25wt% ammonia water and stirring for 1.5-2.5h, then adding tetraethyl orthosilicate and stirring for 24h, filtering, collecting the product, and redispersing it in ethanol, then slowly adding 3-bromopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane dropwise, and stirring at room temperature for 8-12h, filtering, collecting the product, and then dispersing it in a hydrochloric acid ethanol solution (the volume ratio of hydrochloric acid to ethanol is 1:6), and transferring it to an oil bath pot, refluxing at 70°C for 8-12h, filtering, washing, and drying to obtain mesoporous silica (MS); Further, in step A1, the usage ratio of hexadecyltrimethylammonium bromide, deionized water, ammonia water, tetraethyl orthosilicate, ethanol, 3-bromopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and ethanolic hydrochloric acid solution is 0.7-2.1 g: 150 mL: 5-15 mL: 3-9 mL: 100 mL: 0.3-0.6 mL: 0.3-0.6 mL: 200 mL; Step A2, dispersing zinc nitrate hexahydrate uniformly in deionized water, slowly dropping oleamine and mesoporous silica solution, stirring continuously for 15-30 minutes, centrifuging, washing, and drying in an oven at 120°C for 12 hours to obtain MS / ZnO2 QDs (zinc oxide quantum dots loaded with mesoporous silica); Further, in step A2, the usage ratio of zinc nitrate hexahydrate, deionized water, oleylamine and mesoporous silica solution is 1.1-3.3 g: 50 mL: 1-3 mL: 10 mL; Further, in step A2, the mesoporous silica solution is prepared by mixing mesoporous silica and deionized water in a dosage ratio of 0.5-2 g:10 mL; Step A3, 2,4-dihydroxybenzophenone and potassium carbonate are uniformly dispersed in acetone, and then the MS / ZnO2 QDs acetone solution is added, and refluxed at 45-55° C. for 12-16 hours, filtered, washed, and dried to obtain a reinforced filler; Further, in step A3, the usage ratio of 2,4-dihydroxybenzophenone, potassium carbonate, acetone and MS / ZnO2 QDs acetone solution is 1-3 g: 1.3-3.9 g: 30 mL: 20 mL; Furthermore, in step A3, the MS / ZnO2 QDs acetone solution is prepared by mixing MS / ZnO2 QDs and acetone in a dosage ratio of 0.3-0.8 g: 20 mL.

[0006] The hyperbranched polyimide is prepared by the following steps: Step B1, under nitrogen conditions, disperse pyromellitic anhydride in dimethylacetamide evenly, and slowly add it into the melamine dimethylacetamide solution through a dropping funnel, and stir to react for 15-20 hours to obtain a hyperbranched polyimide precursor; Further, in step B1, the dosage ratio of pyromellitic anhydride, dimethylacetamide and melamine dimethylacetamide solution is 0.03-0.035 mol: 100 mL: 100 mL; Furthermore, the melamine dimethylacetamide solution in step B1 is prepared by mixing and stirring melamine and dimethylacetamide in a dosage ratio of 0.01 mol:100 mL; Step B2, under nitrogen conditions, adding allylamine to the hyperbranched polyimide precursor, stirring the reaction for 5-8 hours, and distilling under reduced pressure to obtain a hyperbranched polyimide; Furthermore, in step B2, the allylamine is 20-30wt% of the mass of pyromellitic dianhydride.

[0007] A method for preparing a pressure-sensitive adhesive protective film comprises the following steps: Step S1, weighing raw materials by weight, mixing high-density polyethylene, maleic anhydride grafted low-density polyethylene, hyperbranched polyimide, reinforcing filler, lubricant, initiator and antioxidant in a blender to obtain a mixture; Step S2: put the mixed material into a twin-screw extruder for melt extrusion, then place it in a stretching device, keep it at 190-210°C for 15 minutes, then cool it to 120-130°C, and heat it for 15-20 seconds. -1 The pressure-sensitive adhesive protective film is obtained by stretching at a stretching rate of and cooling. Furthermore, in step S2, the temperatures of the various sections of the twin-screw extruder are 170-180°C, 190-200°C, 210-220°C, and 190-200°C, respectively, and the screw speed is 30-50rpm.

[0008] Beneficial effects of the present invention: The pressure-sensitive adhesive protective film of the present invention is based on high-density polyethylene as the main matrix, and various functional additives are added to improve the comprehensive performance of the polyethylene film; wherein, maleic anhydride is grafted onto low-density polyethylene to improve the compatibility between the raw materials of the various components of the matrix; hyperbranched polyimide is added to improve the heat resistance and mechanical strength of the agent; reinforcing fillers are added to improve the ultraviolet resistance and transparency of the matrix. Therefore, the polyethylene film of the present invention has a wider application prospect as a protective film for pressure-sensitive adhesives.

[0009] In the reinforcing filler, mesoporous silica with bromine groups and double bond structures on the surface was synthesized by using hexadecyltrimethylammonium bromide as template, tetraethyl orthosilicate as raw material, 3-bromopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane as surface modifiers; zinc oxide quantum dots were loaded on the mesoporous silica using zinc nitrate hexahydrate and oleylamine as raw materials to obtain MS / ZnO2 QDs; finally, the active groups on the surface of MS / ZnO2 QDs reacted with 2,4-dihydroxybenzophenone to obtain the reinforcing filler. After the reinforcing filler is introduced into the matrix, the synergistic effect between mesoporous silica, zinc oxide quantum dots and benzophenone can not only shield ultraviolet rays at the physical level, but also absorb ultraviolet rays, thereby significantly improving the matrix's ultraviolet resistance and avoiding the decline in ultraviolet resistance caused by migration and precipitation of traditional ultraviolet absorbers in the matrix; among them, mesoporous silica as a carrier can provide more active sites for quantum dots, and quantum dots can effectively absorb ultraviolet rays in plastic films due to their unique nano-size structure and surface effects, avoiding damage to the film by ultraviolet rays. At the same time, both silica and quantum dots have excellent transparency, which can improve the transparency of the film. In addition, the reinforcing filler also plays a reinforcing role in polyethylene, improving the mechanical strength of the matrix.

[0010] Hyperbranched polyimide is prepared by first using pyromellitic dianhydride and melamine as raw materials to synthesize a hyperbranched polyimide precursor, and then using the anhydride at the end of the precursor to react with allylamine to obtain a hyperbranched polyimide with a double bond structure at the end. Hyperbranched polyimide can significantly improve the heat resistance and mechanical strength of the matrix in the matrix, because the hyperbranched polyimide has a large number of heat-resistant imide groups, which can maintain stable performance under high temperature conditions; in addition, the rigid benzene ring structure and imide groups in the polyimide molecular chain can form a stable network structure, which can significantly improve the tensile strength and bending strength of the film, so that it can withstand greater external forces without being easily broken or damaged. The double bond structure contained at the end can also cross-link with polyethylene to increase the density of the polyethylene film. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Example 1: The reinforcing filler is prepared by the following steps: Step A1, 0.7g of hexadecyltrimethylammonium bromide was evenly dispersed in 150mL of deionized water, 5mL of 25wt% ammonia water was added and stirred for 1.5h, and then 3mL of tetraethyl orthosilicate was added and stirred for 24h, filtered, the product was collected, and redispersed in 100mL of ethanol, and then 0.3mL of 3-bromopropyltrimethoxysilane and 0.3mL of γ-methacryloxypropyltrimethoxysilane were slowly added dropwise, and stirred at room temperature for 8h, filtered, collected the product, and then dispersed it in 200mL of hydrochloric acid ethanol solution (the volume ratio of hydrochloric acid to ethanol is 1:6), and transferred to an oil bath pot, refluxed at 70°C for 8h, filtered, washed, and dried to obtain mesoporous silica; Step A2, 1.1 g of zinc nitrate hexahydrate was evenly dispersed in 50 mL of deionized water, 1 mL of oleylamine and 10 mL of mesoporous silica solution were slowly added dropwise, stirring was continued for 15 min, centrifuged, washed, and dried in an oven at 120 ° C for 12 h to obtain MS / ZnO2 QDs, wherein the mesoporous silica solution was prepared by mixing mesoporous silica and deionized water in a dosage ratio of 0.5 g: 10 mL; Step A3, disperse 1g 2,4-dihydroxybenzophenone and 1.3g potassium carbonate in 30mL acetone, add 20mL MS / ZnO2 QDs acetone solution, reflux at 45°C for 12h, filter, wash and dry to obtain reinforced filler. The MS / ZnO2 QDs acetone solution is prepared by mixing MS / ZnO2 QDs and acetone in a dosage ratio of 0.3g:20mL.

[0013] Hyperbranched polyimide is prepared by the following steps: Step B1, under nitrogen conditions, 0.03 mol of pyromellitic dianhydride is evenly dispersed in 100 mL of dimethylacetamide, and slowly added into 100 mL of melamine dimethylacetamide solution through a dropping funnel, and stirred for 15 hours to obtain a hyperbranched polyimide precursor polymer, wherein the melamine dimethylacetamide solution is prepared by mixing and stirring melamine and dimethylacetamide in a dosage ratio of 0.01 mol: 100 mL; Step B2: under nitrogen, add allylamine to the hyperbranched polyimide precursor, stir and react for 5 hours, and distill under reduced pressure to obtain a hyperbranched polyimide, wherein the allylamine is 20 wt% of the mass of pyromellitic dianhydride.

[0014] Example 2: The reinforcing filler is prepared by the following steps: Step A1, 1.4g hexadecyltrimethylammonium bromide was evenly dispersed in 150mL deionized water, 10mL of 25wt% ammonia water was added and stirred for 2h, then 6mL of tetraethyl orthosilicate was added and stirred for 24h, filtered, the product was collected, and redispersed in 100mL of ethanol, and then 0.45mL of 3-bromopropyltrimethoxysilane and 0.45mL of γ-methacryloxypropyltrimethoxysilane were slowly added dropwise, and stirred at room temperature for 10h, filtered, collected the product, and then dispersed it in 200mL of hydrochloric acid ethanol solution (the volume ratio of hydrochloric acid to ethanol is 1:6), and transferred to an oil bath pot, refluxed at 70°C for 10h, filtered, washed, and dried to obtain mesoporous silica; Step A2, 2.2 g of zinc nitrate hexahydrate was evenly dispersed in 50 mL of deionized water, 2 mL of oleylamine and 10 mL of mesoporous silica solution were slowly added dropwise, stirring was continued for 25 min, centrifuged, washed, and dried in an oven at 120 ° C for 12 h to obtain MS / ZnO2 QDs, wherein the mesoporous silica solution was prepared by mixing mesoporous silica and deionized water in a dosage ratio of 1 g: 10 mL; Step A3, 2 g of 2,4-dihydroxybenzophenone and 2.6 g of potassium carbonate are evenly dispersed in 30 mL of acetone, and then 20 mL of MS / ZnO2 QDs acetone solution is added, refluxed at 50°C for 14 h, filtered, washed, and dried to obtain a reinforced filler. The MS / ZnO2 QDs acetone solution is prepared by mixing MS / ZnO2 QDs and acetone in a dosage ratio of 0.5 g:20 mL.

[0015] Hyperbranched polyimide is prepared by the following steps: Step B1, under nitrogen conditions, 0.032 mol of pyromellitic dianhydride is evenly dispersed in 100 mL of dimethylacetamide, and slowly added into 100 mL of melamine dimethylacetamide solution through a dropping funnel, and stirred for 17 hours to obtain a hyperbranched polyimide precursor polymer, wherein the melamine dimethylacetamide solution is prepared by mixing and stirring melamine and dimethylacetamide in a dosage ratio of 0.01 mol: 100 mL; Step B2: under nitrogen, add allylamine to the hyperbranched polyimide precursor, stir and react for 6.5 hours, and distill under reduced pressure to obtain a hyperbranched polyimide, wherein the allylamine is 25 wt% of the mass of pyromellitic dianhydride.

[0016] Example 3: The reinforcing filler is prepared by the following steps: Step A1, 2.1g hexadecyltrimethylammonium bromide was evenly dispersed in 150mL deionized water, 15mL of 25wt% ammonia water was added and stirred for 2.5h, and then 9mL of tetraethyl orthosilicate was added and stirred for 24h, filtered, the product was collected, and redispersed in 100mL of ethanol, and then 0.6mL of 3-bromopropyltrimethoxysilane and 0.6mL of γ-methacryloxypropyltrimethoxysilane were slowly added dropwise, and stirred at room temperature for 12h, filtered, collected the product, and then dispersed it in 200mL of hydrochloric acid ethanol solution (the volume ratio of hydrochloric acid to ethanol is 1:6), and transferred to an oil bath pot, refluxed at 70°C for 12h, filtered, washed, and dried to obtain mesoporous silica; Step A2, 3.3 g of zinc nitrate hexahydrate was evenly dispersed in 50 mL of deionized water, 3 mL of oleylamine and 10 mL of mesoporous silica solution were slowly added dropwise, stirring was continued for 30 min, centrifuged, washed, and dried in an oven at 120 ° C for 12 h to obtain MS / ZnO2 QDs, wherein the mesoporous silica solution was prepared by mixing mesoporous silica and deionized water in a dosage ratio of 2 g: 10 mL; Step A3, 3g 2,4-dihydroxybenzophenone and 3.9g potassium carbonate are evenly dispersed in 30mL acetone, and then 20mL MS / ZnO2 QDs acetone solution is added, refluxed at 55°C for 16h, filtered, washed and dried to obtain a reinforced filler. The MS / ZnO2 QDs acetone solution is prepared by mixing MS / ZnO2 QDs and acetone in a dosage ratio of 0.8g:20mL.

[0017] Hyperbranched polyimide is prepared by the following steps: Step B1, under nitrogen conditions, 0.035 mol of pyromellitic dianhydride is evenly dispersed in 100 mL of dimethylacetamide, and slowly added into 100 mL of melamine dimethylacetamide solution through a dropping funnel, and stirred for 20 hours to obtain a hyperbranched polyimide precursor polymer, wherein the melamine dimethylacetamide solution is prepared by mixing and stirring melamine and dimethylacetamide in a dosage ratio of 0.01 mol: 100 mL; Step B2: under nitrogen, add allylamine to the hyperbranched polyimide precursor, stir and react for 8 hours, and distill under reduced pressure to obtain a hyperbranched polyimide, wherein the allylamine is 30 wt% of the mass of pyromellitic dianhydride.

[0018] Embodiment 4: A method for preparing a pressure-sensitive adhesive protective film comprises the following steps: 60 parts of high-density polyethylene, 8 parts of maleic anhydride grafted low-density polyethylene, 15 parts of the hyperbranched polyimide prepared in Example 1, 8 parts of the reinforcing filler prepared in Example 1, 1 part of zinc stearate, 0.1 parts of benzoyl peroxide, and 1 part of antioxidant 1010; Step S1, weighing raw materials by weight, mixing high-density polyethylene, maleic anhydride grafted low-density polyethylene, the hyperbranched polyimide prepared in Example 1, the reinforcing filler prepared in Example 1, zinc stearate, benzoyl peroxide and antioxidant 1010 in a blender to obtain a mixture; Step S2: put the mixed material into a twin-screw extruder for melt extrusion, then place it in a stretching device, keep it at 190°C for 15 minutes, then cool it to 120°C for 15 seconds. -1 The pressure-sensitive adhesive protective film is obtained by stretching at a stretching rate of and cooling. The temperatures of each section of the twin-screw extruder are 170°C, 190°C, 210°C, and 190°C, respectively, and the screw speed is 30rpm.

[0019] Embodiment 5: A method for preparing a pressure-sensitive adhesive protective film comprises the following steps: 70 parts of high-density polyethylene, 12 parts of maleic anhydride grafted low-density polyethylene, 20 parts of the hyperbranched polyimide prepared in Example 2, 12 parts of the reinforcing filler prepared in Example 2, 1.5 parts of zinc stearate, 0.1 parts of benzoyl peroxide, and 10101 parts of an antioxidant; Step S1, weighing raw materials by weight, mixing high-density polyethylene, maleic anhydride grafted low-density polyethylene, the hyperbranched polyimide prepared in Example 2, the reinforcing filler prepared in Example 2, zinc stearate, benzoyl peroxide and antioxidant 1010 in a blender to obtain a mixture; Step S2: put the mixed material into a twin-screw extruder for melt extrusion, then place it in a stretching device, keep it at 200°C for 15 minutes, then cool it to 125°C for 20 seconds. -1 The pressure-sensitive adhesive protective film is obtained by stretching at a stretching rate of and cooling. The temperatures of each section of the twin-screw extruder are 175°C, 195°C, 215°C, and 195°C, respectively, and the screw speed is 40rpm.

[0020] Embodiment 6: A method for preparing a pressure-sensitive adhesive protective film comprises the following steps: 80 parts of high-density polyethylene, 15 parts of maleic anhydride grafted low-density polyethylene, 25 parts of the hyperbranched polyimide prepared in Example 3, 15 parts of the reinforcing filler prepared in Example 3, 2 parts of zinc stearate, 0.2 parts of benzoyl peroxide, and 3 parts of antioxidant 1010; Step S1, weighing raw materials by weight, mixing high-density polyethylene, maleic anhydride grafted low-density polyethylene, the hyperbranched polyimide prepared in Example 3, the reinforcing filler prepared in Example 3, zinc stearate, benzoyl peroxide and antioxidant 1010 in a blender to obtain a mixture; Step S2: The mixed material is put into a twin-screw extruder for melt extrusion, and then placed in a stretching device, maintained at 210°C for 15 minutes, and then cooled to 130°C for 20 seconds.-1 The pressure-sensitive adhesive protective film is obtained by stretching at a stretching rate of and cooling. The temperatures of each section of the twin-screw extruder are 180°C, 200°C, 220°C, and 200°C, respectively, and the screw speed is 50rpm.

[0021] Comparative Example 1: This comparative example is a pressure-sensitive adhesive protective film, which is different from Example 6 in that commercially available polyimide is used instead of the hyperbranched polyimide prepared in Example 3, and the rest are the same.

[0022] Comparative Example 2: This comparative example is a pressure-sensitive adhesive protective film. The difference from Example 6 is that the MS / ZnO2 QDs prepared in Example 3 replaces the reinforcing filler prepared in Example 3, and the rest are the same.

[0023] Comparative Example 3: This comparative example is a pressure-sensitive adhesive protective film. The difference from Example 6 is that silicon dioxide is used instead of the reinforcing filler prepared in Example 3, and 1-2 parts of 2,4-dihydroxybenzophenone are added, and the rest are the same.

[0024] The performance of the pressure-sensitive adhesive protective films prepared in Examples 4-6 and Comparative Examples 1-3 was tested: Mechanical properties test: refer to GB / T 1040.3-2006 standard to test tensile strength and elongation at break; Heat resistance test: Test the thermal shrinkage of samples with an average thickness of 25um (120℃, 30min); UV resistance test: The sample was subjected to UV aging test under the following conditions: temperature of 60°C, irradiance of 0.89W / m²·nm, irradiation time of 7d, and its tensile strength and elongation at break were tested; The test results are shown in Table 1: Table 1: Performance test results

[0025] It can be seen from Table 1 that the pressure-sensitive adhesive protective film prepared by the present invention has excellent UV resistance, heat resistance, tensile strength and elongation at break.

[0026] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A pressure-sensitive adhesive protective film, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of high-density polyethylene, 8-15 parts of maleic anhydride grafted low-density polyethylene, 15-25 parts of hyperbranched polyimide, 8-15 parts of reinforcing filler, 1-2 parts of lubricant, 0.1-0.2 parts of initiator, and 1-3 parts of antioxidant; The reinforcing filler is prepared by the following steps: Step A1, dispersing hexadecyltrimethylammonium bromide uniformly in deionized water, adding 25wt% ammonia water and stirring for 1.5-2.5h, then adding tetraethyl orthosilicate and stirring for 24h, filtering, collecting the product, and redispersing it in ethanol, then slowly adding 3-bromopropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane dropwise, and stirring at room temperature for 8-12h, filtering, collecting the product, and then dispersing it in hydrochloric acid ethanol solution, and transferring it to an oil bath pot, reflux at 70°C for 8-12h, filtering, washing, and drying to obtain mesoporous silica; Step A2, dispersing zinc nitrate hexahydrate evenly in deionized water, slowly dropping oleamine and mesoporous silica solution, stirring continuously for 15-30 min, centrifuging, washing, and drying in an oven at 120°C for 12 h to obtain MS / ZnO2 QDs; Step A3, 2,4-dihydroxybenzophenone and potassium carbonate are dispersed uniformly in acetone, and then the MS / ZnO2 QDs acetone solution is added, and refluxed at 45-55° C. for 12-16 hours, filtered, washed, and dried to obtain a reinforced filler.

2. A pressure-sensitive adhesive protective film according to claim 1, characterized in that: In step A1, the usage ratio of hexadecyltrimethylammonium bromide, deionized water, ammonia water, tetraethyl orthosilicate, ethanol, 3-bromopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and ethanolic hydrochloric acid solution is 0.7-2.1 g: 150 mL: 5-15 mL: 3-9 mL: 100 mL: 0.3-0.6 mL: 0.3-0.6 mL: 200 mL.

3. A pressure-sensitive adhesive protective film according to claim 1, characterized in that: Furthermore, in step A2, the dosage ratio of zinc nitrate hexahydrate, deionized water, oleylamine and mesoporous silica solution is 1.1-3.3 g:50 mL:1-3 mL:10 mL, and the mesoporous silica solution is prepared by mixing mesoporous silica and deionized water in a dosage ratio of 0.5-2 g:10 mL.

4. A pressure-sensitive adhesive protective film according to claim 1, characterized in that: In step A3, the dosage ratio of 2,4-dihydroxybenzophenone, potassium carbonate, acetone and MS / ZnO2 QDs acetone solution is 1-3 g: 1.3-3.9 g: 30 mL: 20 mL, and the MS / ZnO2 QDs acetone solution is prepared by mixing MS / ZnO2 QDs and acetone in a dosage ratio of 0.3-0.8 g: 20 mL.

5. The pressure-sensitive adhesive protective film according to claim 1, characterized in that: The hyperbranched polyimide is prepared by the following steps: Step B1, under nitrogen conditions, disperse pyromellitic anhydride in dimethylacetamide evenly, and slowly add it into the melamine dimethylacetamide solution through a dropping funnel, and stir the reaction for 15-20 hours to obtain a hyperbranched polyimide precursor; ‌ Step B2: under nitrogen, add allylamine to the hyperbranched polyimide precursor, stir and react for 5-8 hours, and perform vacuum distillation to obtain the hyperbranched polyimide.

6. A pressure-sensitive adhesive protective film according to claim 5, characterized in that: Furthermore, in step B1, the dosage ratio of pyromellitic anhydride, dimethylacetamide and melamine dimethylacetamide solution is 0.03-0.035 mol:100 mL:100 mL, and the melamine dimethylacetamide solution is prepared by mixing and stirring melamine and dimethylacetamide in a dosage ratio of 0.01 mol:100 mL.

7. A pressure-sensitive adhesive protective film according to claim 5, characterized in that: In step B2, the allylamine is 20-30wt% of the mass of pyromellitic dianhydride.

8. A method for preparing the pressure-sensitive adhesive protective film according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, mixing high-density polyethylene, maleic anhydride grafted low-density polyethylene, hyperbranched polyimide, reinforcing filler, lubricant, initiator and antioxidant in a blender to obtain a mixture; Step S2: put the mixed material into a twin-screw extruder for melt extrusion, then place it in a stretching device, keep it at 190-210°C for 15 minutes, then cool it to 120-130°C, and heat it for 15-20 seconds. -1 The pressure-sensitive adhesive protective film is obtained by stretching at a stretching rate of and cooling.

9. The method for preparing a pressure-sensitive adhesive protective film according to claim 8, characterized in that: In step S2, the temperatures of each section of the twin-screw extruder are 170-180° C., 190-200° C., 210-220° C., and 190-200° C., respectively, and the screw speed is 30-50 rpm.

Citation Information

Patent Citations

  • Preparation method for zinc oxide anti-microbial composite material

    CN105494434A

  • Ultraviolet aging resistant biodegradable film as well as preparation method and application thereof

    CN112341769A

  • Crosslinkable polyethylene composition, crosslinked polyethylene and preparation method thereof, crosslinked polyethylene product and preparation method and application thereof

    CN113913053A